Chemical and thermal ocular burns: a review of causes, clinical features and management protocol - Khathutshelo Mashige (South African Family Practice)
Chemical and thermal ocular burns are among the most urgent ophthalmic emergencies, often resulting in permanent damage, and in some cases, blindness. These burns are the result of exposure to chemicals or radiant energy (thermal or ultraviolet). The most serious injuries are due to chemical burns by strong acid or bases. The purpose of managing these burns is to eliminate or limit the causative agent from penetrating the ocular structures by irrigation; and, promoting ocular surface healing through medical and surgical intervention. This review presents a current update on the causes of chemical and thermal ocular burns, their clinical features and the importance of appropriate and prompt treatment.